Towards developing novel and sustainable molecular light-to-heat converters. Issue 46 (10th November 2021) - Abiola, Temitope T.; Rioux, Benjamin; Toldo, Josene M.; Alarcan, Jimmy; Woolley, Jack M.; Turner, Matthew A. P.; Coxon, Daniel J. L.; Telles do Casal, Mariana; Peyrot, Cédric; Mention, Matthieu M.; Buma, Wybren J.; Ashfold, Michael N. R.; et al.
Abstract : The synthesis and photophysical properties of phenolic barbiturics are reported. These molecules convert absorbed ultraviolet light to heat with high fidelity and may be suitable for inclusion in foliar sprays to boost crop protection and production. Abstract : Light-to-heat conversion materials generate great interest due to their widespread applications, notable exemplars being solar energy harvesting and photoprotection. Another more recently identified potential application for such materials is in molecular heaters for agriculture, whose function is to protect crops from extreme cold weather and extend both the growing season and the geographic areas capable of supporting growth, all of which could help reduce food security challenges. To address this demand, a new series of phenolic-based barbituric absorbers of ultraviolet (UV) radiation has been designed and synthesised in a sustainable manner. The photophysics of these molecules has been studied in solution using femtosecond transient electronic and vibrational absorption spectroscopies, allied with computational simulations and their potential toxicity assessed by in silico studies. Following photoexcitation to the lowest singlet excited state, these barbituric absorbers repopulate the electronic ground state with high fidelity on an ultrafast time scale (within a few picoseconds). The energy relaxation pathway includes a twisted intramolecular charge-transfer state as the system evolves out of the Franck–Condon region, internal conversion to the ground electronic state, and subsequent vibrational cooling. These barbituric absorbers display promising light-to-heat conversion capabilities, are predicted to be non-toxic, and demand further study within neighbouring application-based fields.